Evaluation and Re-Estimation of Bankruptcy Prediction Models in Facing The Crisis Period in Indonesia (2017-2022) - Lubis, Mentari M.; Gandakusuma, Imo (Syntax Corporation, 2024)
This research was conducted to see how suitable the existing bankruptcy prediction models that have been used in other countries to be used during the crisis in Indonesia. The data used in research are companies in Indonesia registered in the Indonesia Stock Exchange (IDX). The re-estimate of the coefficient of variables models is carried out and then the bankruptcy prediction of the re-estimation model is re-calculated. The results of the bankruptcy prediction of the re-estimate model are then compared with the results of the bankruptcy prediction of the original model to see whether the model can be used during the crisis in Indonesia. The results of the study is that Springate original model is the most suitable model for the conditions in Indonesia during the crisis caused by the COVID-19 pandemic. The Springate model has the highest financial distress prediction accuracy, while the Altman Emerging Market model produces the highest Error Type I.